Examining perinatal health inequities: The role of disability and risk of adverse outcomes through the U.S. Pregnancy Risk Assessment Monitoring System. - Jeanne L Alhusen; Genevieve R Lyons; Rosemary B Hughes; Kathryn Laughon; Maria McDonald; Casey L Johnson (PLoS ONE)
Objective To examine pre-pregnancy characteristics, pregnancy complications, and birth outcomes among respondents with self-reported disability compared to those without disability. Methods A cross-sectional weighted sample of 2,006,700 respondents with singleton live births who participated in the United States Pregnancy Risk Assessment Monitoring System (PRAMS) between 2018 and 2021 provided data on disability, including difficulty in vision, hearing, ambulation, cognition, communication, and self-care. We estimated covariate-adjusted odds of differences in pre-pregnancy chronic health conditions, pregnancy intention, intimate partner violence (IPV), depression, adequacy of prenatal care, pregnancy-related health conditions, and birth outcomes by disability status. Results Of the 2,006,700 respondents included, 59.5% reported no disability, 33.9% had moderate disability, and 6.6% had severe disability. Across most outcomes, there was a graded pattern with those with severe disability having the worst outcomes compared to the other two groups. Respondents with severe disability were more likely to report diabetes and hypertension before becoming pregnant than respondents without disabilities. Those respondents with severe disability or moderate disability had an increased odds of reporting IPV and depression than those with no disability. During pregnancy, respondents with severe disability had an increased odds of gestational diabetes (aOR 1.46, 95% CI 1.18, 1.80) and hypertensive disorders of pregnancy (aOR 1.70, 95% CI 1.43, 2.02) as compared to respondents with no disability. Respondents with moderate disability also had an increased odds of both gestational diabetes (aOR 1.19, 95% CI 1.06, 1.34) and hypertensive disorders of pregnancy (aOR 1.29, 95% CI 1.17, 1.42) as compared to those with no disability. The odds of reporting an unintended pregnancy were highest in respondents with a severe disability (aOR 1.66, 95% CI 1.43, 1.94) and were also increased in respondents with moderate disability (aOR 1.48, 95% CI 1.36, 1.62) as compared to those reporting no disability. Across most birth outcomes, respondents with severe disabilities had worse outcomes with an increased odds of low birth weight infants (aOR 1.28, 95% CI 1.08, 1.52), preterm birth (aOR 1.32, 95% CI 1.11, 1.57), and neonatal intensive care unit admission (aOR 1.45, 95% CI 1.02, 2.06) as compared to respondents with no disability. There were not differences in being classified as small for gestational age or infants' length of hospital stay by disability status. Conclusions Across the perinatal period, respondents with moderate or severe disability experienced worse outcomes than those without disability. There is a critical need to improve pre-conception health in an effort to reduce inequities in pregnancy outcomes. Additionally, health care providers and systems must provide equitable access to care to persons with disabilities to reduce inequities in outcomes.